2019
DOI: 10.1177/0363546519833684
|View full text |Cite|
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Repair With Collagen-Dipped FiberTape Augmentation in Overhead-Throwing Athletes

Abstract: Background: There has been a renewed interest in ulnar collateral ligament (UCL) repair in overhead athletes because of a greater understanding of UCL injuries, an improvement in fixation technology, and the extensive rehabilitation time to return to play. Purpose/Hypothesis: To evaluate the clinical outcomes of a novel technique of UCL repair with internal brace augmentation in overhead throwers. Study Design: Case series; Level of evidence, 4. Methods: Patients undergoing a novel technique of UCL repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
128
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 17 publications
2
128
0
3
Order By: Relevance
“…8,18 Savoie et al 27 published findings on a series of UCL repairs for 60 high school and college athletes, reporting 93% with good-to-excellent outcomes and return to play within 6 months of surgery. More recently, Dugas et al 7 found similar outcomes in 111 high school and college athletes, reporting that 92% returned to the same or higher level of competition at an average of 7 months after UCL repair with internal brace augmentation.…”
mentioning
confidence: 83%
“…8,18 Savoie et al 27 published findings on a series of UCL repairs for 60 high school and college athletes, reporting 93% with good-to-excellent outcomes and return to play within 6 months of surgery. More recently, Dugas et al 7 found similar outcomes in 111 high school and college athletes, reporting that 92% returned to the same or higher level of competition at an average of 7 months after UCL repair with internal brace augmentation.…”
mentioning
confidence: 83%
“…Recently, a modification of the repair was introduced, in which the repair was augmented with a synthetic tape fixed with bone anchors at both ends (InternalBrace®; Arthrex, Naples, FL, USA) to prevent excessive stress on the repaired UCL and might permanently reinforce the healed ligament ( Fig. 4 ) [ 25 , 26 ].…”
Section: Treatmentmentioning
confidence: 99%
“…2 In a clinical study, Dugas et al performed UCL repair with collagen-dipped suture bridge augmentation in overhead athletes and found a 92% return to sport and shortened time to return (6.7 months) compared to UCL reconstruction. 9 An accelerated rehabilitation program may be appropriate for patients who are compliant and desire to return to a higher level of competition.…”
mentioning
confidence: 99%